1997
DOI: 10.1088/0953-4075/30/13/013
|View full text |Cite
|
Sign up to set email alerts
|

State propensities in electron transfer processes from optically prepared states:

Abstract: This paper reports experimental and theoretical results for the influence of optical target preparation on electron transfer for the H + − Na(3s, 3p) collision system at a proton impact energy of 2 keV. The spatial pattern of the forwardly scattered neutrals is found to depend sensitively on initial optical target preparation as well as on the energy defect of the process. The complete set of density matrix parameters has been determined for the channels corresponding to electron transfer into H(n = 2) and H(n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The study of charge transfer dynamics from laser-excited Na(3p) atoms has been mostly focused on collision energies corresponding to velocities around and below the expectation value of the electron velocity in the initial Na(3p) state [1][2][3]. At these projectile energies it is now well established that an expansion of the wavefunction in either atomic (AO) or molecular (MO) basis states is adequate and, in general, gives an excellent agreement with experiments for total and partial cross sections [4] and phase-dependent coherence parameters [3,5]. Recently, it has also been demonstrated that the classical trajectory Monte Carlo (CTMC) method gives the correct relative distribution for the H(n = 2) channels in capture from laser-excited Na(3p −1 ) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of charge transfer dynamics from laser-excited Na(3p) atoms has been mostly focused on collision energies corresponding to velocities around and below the expectation value of the electron velocity in the initial Na(3p) state [1][2][3]. At these projectile energies it is now well established that an expansion of the wavefunction in either atomic (AO) or molecular (MO) basis states is adequate and, in general, gives an excellent agreement with experiments for total and partial cross sections [4] and phase-dependent coherence parameters [3,5]. Recently, it has also been demonstrated that the classical trajectory Monte Carlo (CTMC) method gives the correct relative distribution for the H(n = 2) channels in capture from laser-excited Na(3p −1 ) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[15,16]. For capture from excited states the situation is less clear, but there are recent results for low collision energy [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…Note that, in the mean time, alignment [4] and orientation measurements with laser excited alkali targets had developed to establish propensity rules from the reversed process [10].…”
Section: In What Sense Is the Captured Electron Rotating ?mentioning
confidence: 99%
“…Electron transfer in ion-atom collisions has been widely investigated and is still a very active field [1][2][3][4][5][6][7][8][9]. Collisions of bare nuclei on H atoms have been of primary interest and have led to elaborate calculations.…”
Section: Introductionmentioning
confidence: 99%